Proceedings of the 2019 Federated Conference on Computer Science and Information Systems 2019
DOI: 10.15439/2019f323
|View full text |Cite
|
Sign up to set email alerts
|

ICT Usage in Industrial Symbiosis: Problem Identification and Study Design

Abstract: Industrial symbiosis is a favored approach to balancing industry's economic growth and its environmental impact on a regional scale. Although the scientific literature reports a multitude of examples of industrial symbiosis around the world, this approach and its related concepts are not considered to be widespread in practice, due to various barriers. Information and management barriers are seen as significant obstacles to industrial symbiosis; however, they have not been adequately investigated yet. Empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 32 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…A non-systematic, targeted literature search was performed to appropriately address the topic of IS, utilizing among others, papers and knowledge gained during preparation of a previously performed by our team systematic literature review [8], for the adjustment of the CE matchmaking framework for IS. For the design of level A of the framework, a set of questions targeting the stakeholders' adoption level of IS practices was developed according to identified studies employing questionnaires related to IS [2], [7], [9]- [11]. For the selection of the benchmarks used within the proposed framework, studies deliberating on matchmaking criteria were identified and further utilized in the design of levels B and C [2], [5], [6], [10], [12]- [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-systematic, targeted literature search was performed to appropriately address the topic of IS, utilizing among others, papers and knowledge gained during preparation of a previously performed by our team systematic literature review [8], for the adjustment of the CE matchmaking framework for IS. For the design of level A of the framework, a set of questions targeting the stakeholders' adoption level of IS practices was developed according to identified studies employing questionnaires related to IS [2], [7], [9]- [11]. For the selection of the benchmarks used within the proposed framework, studies deliberating on matchmaking criteria were identified and further utilized in the design of levels B and C [2], [5], [6], [10], [12]- [14].…”
Section: Methodsmentioning
confidence: 99%
“…For the design of level A of the framework, a set of questions targeting the stakeholders' adoption level of IS practices was developed according to identified studies employing questionnaires related to IS [2], [7], [9]- [11]. For the selection of the benchmarks used within the proposed framework, studies deliberating on matchmaking criteria were identified and further utilized in the design of levels B and C [2], [5], [6], [10], [12]- [14].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, interest in environmentally sustainable industrial and business models has increased, as society’s demand for resources has accelerated and related environmental problems (water scarcity, raw materials’ depletion and waste accumulation) have emerged. Industrial symbiosis (IS) is a sustainable, resource efficient and eco-friendly industrial waste management approach with long-term perspective ( Kosmol & Leyh, 2019 ; Lawal et al , 2021 ; Marconi et al , 2018 ). Initially, the term ‘industrial symbiosis’ referred to the physical exchange of material (waste, stock, by-product), energy, and/or water between geographically close companies.…”
Section: Introductionmentioning
confidence: 99%
“…This exchange involves a company’s output residual flow being used by another company as input flow, so both gain profit and reduce their environmental impact. Presently, IS applies to all interfirm cooperation models, consisting of either exchange or sharing of underutilized resources, utilities, infrastructure, and services in order to achieve a green, waste-free supply chain ( Fraccascia & Yazan, 2018 ; Kosmol, 2019 ; Kosmol & Leyh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation